Gent verkend : informatiegids voor de student van de UGent. (Gent : [UG], 2003)
Fonds Suzan Daniel (FSD)
Periodiciteit : jaarlijks
Redactie : Sint-Pietersnieuwstraat 45, 9000 Gent
Nederlands
Periodiek